Refinements of the ICF Linking Rules to strengthen their potential for establishing comparability of health information. Issue 5 (27th February 2019) - Cieza, Alarcos; Fayed, Nora; Bickenbach, Jerome; Prodinger, Birgit
Abstract: Purpose The content of and methods for collecting health information often vary across settings and challenge the comparability of health information across time, individuals or populations. The International Classification of Functioning, Disability and Health (ICF) contains an exhaustive set of categories of information which constitutes a unified and consistent language of human functioning suitable as a reference for comparing health information. Methods and results In two earlier papers, we have proposed rules for linking existing health information to the ICF. Further refinements to these existing ICF Linking Rules are presented in this paper to enhance the transparency of the linking process. The refinements involve preparing information for linking, perspectives from which information is collected and the categorization of response options. Issues regarding the linking of information not covered or unspecified within the ICF are also revisited in this paper. Conclusion: The ICF Linking Rules are valuable for enhancing comparability of health information to ensure that information is available in a consistent manner to serve as a foundation for evidence-based decision-making across all levels of health systems. The refinements presented in this paper enhance transparency in, and ultimately reliability of the process of, linking health information to the ICF. Implications for Rehabilitation: The International Classification of Functioning, Disability and Health (ICF) constitutes a unified and consistent language of human functioning suitable as a reference for comparing health information. Comparability of information is essential to ensure that the widest range of information is available in a consistent manner for any decision-maker at all levels of the health system. The refined ICF Linking Rules presented in this article outline the method to establish comparability of health information based on the ICF.